2018
DOI: 10.1002/hep.29557
|View full text |Cite
|
Sign up to set email alerts
|

Portal pressure and liver stiffness measurements in the prediction of fibrosis regression after sustained virological response in recurrent hepatitis C

Abstract: In conclusion, SVR post-LT induces fibrosis regression in most patients, leading to significant clinical benefits. Pretreatment HVPG and LSM are significant determinants of the likelihood of fibrosis regression. Finally, LSM accurately predicts the presence of AF and PH 1 year after SVR and thus can be used to determine monitoring strategies. (Hepatology 2018;67:1683-1694).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
98
0
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 137 publications
(120 citation statements)
references
References 47 publications
(95 reference statements)
6
98
0
5
Order By: Relevance
“…Our results were in good agreement with those of Martini et al and Seifert et al, who reported that early improvement of TE values at SVR24 may be attributed to a great extent to resolution in liver inflammation and edema in LT patients who were treated with sofosbuvir‐based therapy; however, paired biopsies were not performed in both studies . Similarly, a recent study comparing paired biopsies has shown LT patients who remained with persistent necroinflammation in the follow‐up biopsy despite SVR not being associated with fibrosis regression …”
Section: Discussionsupporting
confidence: 92%
“…Our results were in good agreement with those of Martini et al and Seifert et al, who reported that early improvement of TE values at SVR24 may be attributed to a great extent to resolution in liver inflammation and edema in LT patients who were treated with sofosbuvir‐based therapy; however, paired biopsies were not performed in both studies . Similarly, a recent study comparing paired biopsies has shown LT patients who remained with persistent necroinflammation in the follow‐up biopsy despite SVR not being associated with fibrosis regression …”
Section: Discussionsupporting
confidence: 92%
“…Fibrosis regression has been investigated extensively in chronic hepatitis B patients after nucleoside treatment and in CHC patients after interferon treatments with results pointing towards a potential for regression or even resolution at longer follow‐up . A similar effect of DAA therapies is becoming evident and fibrosis regression may also lead to diminished portal hypertension with discrete improvements in portal pressure after DAA therapy . In a small number of patients (n = 4), we observed a trend towards reduced portal hypertension.…”
Section: Discussionmentioning
confidence: 62%
“…The limitations of the study, though, pertain to the lack of histological verification of liver inflammation and fibrosis. However, we and others have previously shown very good associations between the macrophage activation markers and liver inflammation as well as between liver stiffness and fibrosis, even after SVR . Another limitation is that not all patients underwent transient elastography by the same method being either the FibroScan or the ARFI method, however, as the combined and separate associations seem similar, we consider the results valid.…”
Section: Discussionmentioning
confidence: 63%
“…Other studies evaluated the response of IFN‐based therapy using non‐invasive assessments; Poynard et al, 2013 reported regression of cirrhosis in 56% of patients who achieved SVR evaluated by fibro test and TE, also, in another study of 10 year follow‐up there was significant reduction ( P < 0.0001) of fibrosis stage evaluated by FIB‐4 in 2290/4731 (48%) patients who had SVR . Fibrosis regression was also demonstrated in a proportion of patients with SVR post‐liver transplantation …”
Section: Discussionmentioning
confidence: 97%